Impact of Climate Change on Food Security in Kashare Sub-County, Mbarara District. - Agaba, Richard (Kabale University, 2024)
The study examined the impact of climate change on food security in Kashare Sub-County, Mbarara District. The objectives were to identify the causes of climate change in the area, evaluate its effects on crop yields and food security, and explore the adaptation strategies that farmers use to counter climate change impacts on food production and livelihoods. A cross-sectional study design was employed, involving a sample of 105 respondents. Data collection methods included self-administered questionnaires, observations, and interview guides. Data analysis was conducted using Excel to produce descriptive statistics such as frequencies and percentages, which were presented in tables and text. According to the study findings on climate change causes, most respondents cited deforestation as the primary cause, with fewer respondents mentioning factors like industrialization, which ranked last. Unsustainable agricultural practices ranked second, and fossil fuel burning ranked third. Regarding the impact on crop yields and food security, 42.9% of respondents reported a reduction in maize yields as the main consequence, while 9.5% noted declines in other crops like sweet potatoes. Additionally, 33.3% mentioned reduced bean production, and 14.3% observed decreased cassava yields. In terms of adaptation strategies, 38.1% of respondents highlighted crop diversification as the primary approach, while 9.5% mentioned other strategies like agroforestry. Soil conservation practices were noted by 33.3%, and water harvesting techniques by 19.1%. The study recommended that farmers in Kashare Sub-County undertake reforestation efforts to restore natural vegetation, while the government should enforce existing environmental policies, introduce new regulations to reduce greenhouse gas emissions, and promote sustainable land use practices.